Personal Property Securities Act: Concept in Practice - Widdup, Linda (LexisNexis, 2016)
This authoritative work focuses on providing an understanding of the PPSA that can be applied to real world situations as practitioners encounter them in practice. This fourth edition includes comprehensive commentary alongside current case law and legislative updates since the last edition. Equivalent Canadian and Australian case law and legislation is drawn upon for comparative purposes.